2021
DOI: 10.3389/fneur.2021.683051
|View full text |Cite
|
Sign up to set email alerts
|

An Externally Validated Dynamic Nomogram for Predicting Unfavorable Prognosis in Patients With Aneurysmal Subarachnoid Hemorrhage

Abstract: Background: Aneurysmal subarachnoid hemorrhage (aSAH) leads to severe disability and functional dependence. However, no reliable method exists to predict the clinical prognosis after aSAH. Thus, this study aimed to develop a web-based dynamic nomogram to precisely evaluate the risk of poor outcomes in patients with aSAH.Methods: Clinical patient data were retrospectively analyzed at two medical centers. One center with 126 patients was used to develop the model. Least absolute shrinkage and selection operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Our nomogram showed better performance, in spite of requiring only 4 variables for calculating probability versus 5 and 9. Our nomogram might seem consistent with the published performance of the dynamic nomogram (AUC 0.885) ( Hu et al, 2021 ). Smaller data, however, was used for establishing the dynamic nomogram compared with our nomogram.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our nomogram showed better performance, in spite of requiring only 4 variables for calculating probability versus 5 and 9. Our nomogram might seem consistent with the published performance of the dynamic nomogram (AUC 0.885) ( Hu et al, 2021 ). Smaller data, however, was used for establishing the dynamic nomogram compared with our nomogram.…”
Section: Discussionsupporting
confidence: 89%
“…Our nomogram showed better performance. To our knowledge, four nomograms were developed and the performance of the nomograms yielded AUCs ranging from 0.784 to 0.885 ( Zhang et al, 2020 ; Hu et al, 2021 ; Wang et al, 2021 ; Yan et al, 2021 ). Two nomograms reached an AUC of 0.831 and 0.851 for incorporating free fatty acids and SIRI, respectively ( Zhang et al, 2020 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that NLR was negatively correlated with mean cerebral blood flow (mCBF) in brain CT perfusion scan of aSAH patients, and positively correlated with mean transit time (MTT) and mean time to peak (mTTP), suggesting slow and insufficient cerebral blood flow ( 5 ). Many studies have reported that elevated NLR can predict DCI occurrence after aSAH ( 9 , 22 , 23 ), whereas some studies have denied the correlation between them ( 19 ), so we conducted a meta-analysis of relevant literature. As mentioned above, our results show that elevated NLR is significantly correlated with the DCI occurrence after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…The LASSO regression as a special method performs well when reducing data dimensions and multicollinearity among features. For instance, our previous study ( 26 ) used the LASSO method to select three optimal variables for establishing a dynamic nomogram for predicting an unfavorable prognosis after aSAH in the case of limited effective sample size. In this study, the optimal independent risk factor for DCI prediction in elderly patients were CT value of subarachnoid clots and aneurysmal treatment method.…”
Section: Discussionmentioning
confidence: 99%